Institutional Based Social Service and Protection Implementation Effectivity - Rusmiyati, Chatarina; Anggraheni, Rahayu (Jurnal Penelitian Kesejahteraan Sosial, 2018)
This research is meant to know the implementation, goal achievement, handicap and supporting factors of institutional based children service and protection PSAA Tunas Bangsa Pati. Data resources are program implementers that cover structural officials, nurses, functional social workers, service receipients, former receipients, and related stakeholders. From the descriptive analysis can be concluded that the children social care service and protection implementation at PSAA Tunas Bangsa Pati, without parents intervention, has been working optimally as standard model issued by the Ministry of Social Affairs. The service and protection implemented through initial approach, assessment, service plan making, service implementation, resocialization, replacement, advanced guidance, and termination. Though is still found a weakness, that of data based on children with social welfare problem is not provided as data receipients candidates, assessment has not been conducted optimally so that yet can be a base on children service and protection implementation activity. Social guidance is still conducted in a big group so children problem handling has not been yet effective. The guidance of children interest, talent, and skill has not been refered to facilities availability. It needs social workers human resources improvement quantitatively and qualitatively that can support servicing process. The Directorate of Children Social Welfare, General Directorate of Social Rehabilitation as competent institution should establish PSAA to enhance quality of institutional children welfare service together with family based children care model.